Improvement of SUSAN Image Filtering Method for PCB Quality Inspection (Journal of Universal Science Research, 2024)
This paper presents an improvement to the SUSAN image filtering method to improve the quality inspection accuracy of printed circuit boards (PCBs). The problems of traditional filtering methods are considered and improvements are proposed aimed at more effectively removing noise and increasing the reliability of defect detection. The experiments confirm that the modernized SUSAN method provides higher image quality, which is critical for computer vision systems in Industry 4.0. Application of the proposed approach helps reduce defect rates and optimize production processes, improving the overall productivity and reliability of PCB quality control